Growing Entrepreneurial Awareness of the Importance of Business Ethics through Opinion Writing in Online Media: A Study of Community Service in Kompasiana - Hakiki, Moh. Saiful (Indonesia Berdaya, 2023)
Business ethics is an important topic in the context of the modern business world. Poor business ethics can contribute to labor oppression, exploitation of natural resources, environmental pollution, and human rights violations. Conversely, good business ethics can build consumer trust and company reputation. The company is also expected to have social responsibility towards the community and the surrounding environment. Writing online about business ethics has the advantage of reaching a wide audience, raising public awareness, and influencing public opinion. Community service activities aim to foster entrepreneurial awareness of the importance of business ethics, encourage attitude and behavior change, inspire discussion and reflection, and build collaboration networks. The method of community service activities involves identifying target groups, studies and research, writing opinion writing, and publication in online media. It is hoped that this activity can have a positive impact and encourage the adoption of better business ethics among the community.